'Do you know what I mean?' 'Not exactly': English School, global international society and the polysemy of institutions. Issue 3 (3rd July 2015) - Costa-Buranelli,
Abstract : The English School has recently focussed on sub-global political developments, inaugurating a new research agenda on how regional international societies are formed and evolve. However, while regional international societies can adopt more or less institutions than those at the global level, they may take some institutions present at the global level to mean something different. In this paper, it is tentatively argued that the development of regional international societies is favouring the polysemy of institutions, a situation in which different international societies adopt the same institutions with different meanings and specific normative contents. If institutions exist at the global level, but then are framed, interpreted and adopted differently in several regional international societies, then what are the prospects for the existence of a global international society? Does it still make sense to speak of a global international society?